Distribusi Kematian Pasien Penyakit Jantung Bawaan di Instalasi Rawat Inap Anak Rumah Sakit Dokter Soetomo Tahun 2004, 2005, dan 2006 - Agus Cahyono; Machrus A Rachman (Jurnal Kardiologi Indonesia, 2007)
Background. Congenital heart disease (CHD) is a significant cause of mortality in pediatric patients. Meanwhile, malnutrition remains a public health problem in Indonesia. Combined with infection, these condition will increase mortality rate of patients with CHD.Objectives.The objective of this study is to describe the cause of mortal-ity among CHD patients who were hospitalized in pediatric ward, Doctor Soetomo General Hospital, Surabaya during period 2004-2006. Methods. This study is a descriptive evaluation base on Medical Record data.Results. Of patients hospitalized from 2004 to 2006, 189, 185, and 186 respectively grouped into neonatal, infant, and childhood age. Medical record data in 3 years was described into distributive frequency and cross table. Ventricular septal Defect (VSD), Tetralogy of Fallot (TOF), Atrial Septal Defect (ASD), and Patent Ductus Arteriosus (PDA) were the four major CHD. Hospital mortality rate was 11,64% (2004), 11,35% (2005), and 13,44% (2006), infant were the main portion 72,73% (2004), 76,19% (2005), 64% (2006). Respiratory and cardiac failure were two leading cause of death. Fifty percent of death case was underlied by pnemonia and bron-chiolitis. VSD, ASD and TOF were the most common CHD associated with mortality. Death rate was significantly high in malnourished patients, from 2004 to 2006: 45,45% (10/22), 66,67% (14/21), and 72% (18/25) respectively.Conclusions.High mortality rate in our patients with with CHD were associated with age (first year of life), respiratory infections (pnemonia, bronchiolitis), and malnutrition.